Root coverage surgeries using modified tunneling technique of xenogenic collagen matrix versus autologous connective tissue graft as a treatment of Miller class II gingival recession (RCT study) - Ahmed Mortada Fikry Abdel Hamid; Ahmed Wael Aly Abou-Zeid; Mohamed Yehia Saad Abdelfattah (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Recently, there is increased demand for periodontal plastic surgery and development of new surgical approaches for aesthetic purposes. Gingival recession (GR) is the exposure of the root surfaces leading to esthetic problems, hypersensitivity, caries of the roots and teeth loss. Coronally advanced flap is considered a predictable treatment of GR but it needs a filler like subperiosteal connective tissue graft (CTG) which is considered as the gold standard treatment approach. The aim of the present study is to compare the clinical benefits and effectiveness of a xenogenic collagen matrix (mucoderm, botiss, dental, Berlin, Germany) to CTG for treatment of GR. Results Regarding clinical parameters, mean preoperative values for attached gingiva, probing depth, clinical attachment loss and gingival recession for group I were (1.8 ± 0.7 mm, 1.2 ± 0.3 mm, 6.6 ± 0.4 mm and 5.4 ± 0.2 mm) respectively. While mean postoperative values were (2.3 ± 0.9 mm, 1.1 ± 0.4 mm, 3.4 ± 0.5 mm and 2.7 ± 0.7 mm For group two preoperative mean values were (1.9 ± 0.3 mm, 1.1 ± 0.5 mm, 6.8 ± 0.5 mm and 5.4 ± 0.2 mm) respectively. While mean for postoperative values of attached gingiva, probing depth, clinical attachment loss and gingival recession for group tow were (2.5 ± 0.6 mm, 0.8 ± 0.3 mm, 3.7 ± 0.2 mm and 3.1 ± 0.3 mm) respectively All of the clinical parameters measured showed a significant difference between pre ad postoperative measurements while there was no significant differences between the two groups (test and control group). Regarding the patients satisfaction the percentage was greater in test group but the difference was not statistically significant. Conclusions In general, all of the parameters measured showed a significant difference between pre and postoperative measurements for each group but there is no significant difference between the two groups using (two treatment approaches. Both treatment procedures are considered efficient in increasing zone of attached gingiva and decreasing its clinical attachment loss. Mucoderm is considered as an efficient alternative to CTG for treatment of gingival recession.